Circular dichroism and guanine quadruplexes - Vorlíčková, Michaela; Kejnovská, Iva; Sagi, Janos; Renčiuk, Daniel; Bednářová, Klára; Motlová, Jitka; Kypr, Jaroslav (Methods (San Diego, Calif.), 2012)
Circular dichroism (CD) is remarkably sensitive to the conformational states of nucleic acids; therefore, CD spectroscopy has been used to study most features of DNA and RNA structures. Quadruplexes are among the significant noncanonical nucleic acids architectures that have received special attentions recently. This article presents examples on the contribution of CD spectroscopy to our knowledge of quadruplex structures and their polymorphism. The examples were selected to demonstrate the potential of this simple method in the quadruplex field. As CD spectroscopy detects only the global feature of a macromolecule, it should preferably be used in combination with other techniques. On the other hand, CD spectroscopy, often as a pioneering approach, can reveal the formation of particular structural arrangements, to search for the conditions stabilizing the structures, to follow the transitions between various structural states, to explore kinetics of their appearance, to determine thermodynamic parameters and also detect formation of higher order structures. This article aims to show that CD spectroscopy is an important complementary technique to NMR spectroscopy and X-ray diffraction in quadruplex studies.
Keywords: DNA; Thermodynamics; termodynamika; konformace nukleové kyseliny; kinetika; G-kvadruplexy; Nucleic Acid Conformation; Oligonucleotides; oligonukleotidy; X-Ray Diffraction; Guanine; guanin; Kinetics; G-Quadruplexes; difrakce rentgenového záření; cirkulární dichroismus; Circular Dichroism